(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of the level of compliance with ISO/IEC 27001 requirements on cybersecurity in Libyan commercial banks, considering the increasing adoption of digital systems and electronic banking services and the growing cyber threats associated with digital transformation. The study adopted a descriptive analytical approach and used a questionnaire to collect data from employees in information security, information technology, risk management, and internal audit departments in Libyan commercial banks. A total of (26) valid questionnaire were analysed using SPSS through Cronbach’s Alpha, Pearson correlation, and multiple regression analysis. The findings revealed that the level of compliance with ISO/IEC 27001 requirements and the level of cybersecurity were high. The results also showed a statistically significant positive relationship between ISO/IEC 27001 compliance dimensions and cybersecurity, and that these dimensions explain (65.8%) of the variation in cybersecurity level. Cybersecurity risk management was found to have the strongest impact, followed by technical and procedural controls and information security governance, while security awareness and human factors require further improvement. The study recommends strengthening ISO/IEC 27001 implementation, developing cybersecurity awareness and training programs, and improving cybersecurity risk management practices to enhance information protection and ensure business continuity in the banking sector.